Aktivitas Antioksidan Ekstrak Etanol Daun Buas-Buas (Premna cordifolia Linn.) terhadap Gambaran Histopatologi Paru Tikus (Rattus norvegicus) Wistar Jantan Pasca Paparan Asap Rokok - Kristina Lusty Tohomi; Iswahyudi Iswahyudi; Sri Wahdaningsih (Journal of Tropical Pharmacy and Chemistry, 2014)
Cigarette smoke is one of free radical source that can cause oxidative stress, emphysema, and inflamation on lung. Leaves of Premna cordifolia Linn. is one of antioxidant that can neutralize the free radical in body. The purpose of the research  is to find the antioxidant activity of Premna cordifolia leaves in reducing lungâ€™s damage and to find the effective dose that can reduce lungâ€™s damage after exposure of cigarette smoke. Dried leaves of Premna cordifolia are maserated with ethanol 70%.  Rats are divided into five groups, Group without treatment (CMC control), group that exposed to smoke, three groups that treated with 200 (P1), 400 (P2), and 600mg/kgBW (P3) of ethanolic extract of Premna cordifolia leaves after smoke exposure, and one group that treated with 18mg/kgBW of vitamin E as positive control after smoke exposure. All groups were treated with three cigarette without filter for 14 days. All rat were terminated on the fifteent day. Right lung were collected and subjected to necropsy and stained with Hematoksilin-Eosin. The result show that all doses of ethanolic extract of Premna cordifolia reduce lung damage in enlarge alveolar, thickening of alveolarâ€™s wall, and infiltration of inflmation cells in rats. The effective dose is 600mg/kgbw because the potential of Premna cordifolia leaves extract was same with the potential of positive contol in reducing the lung damage.